Artifacts of optical coherence tomography - A. A. Shpak; M. V. Korobkova (Российский офтальмологический журнал, 2019)
Purpose. To study and classify artifacts of spectral-domain optical coherence tomography (OCT).  Material and methods. The retrospective study included OCT data of 112 patients (112 eyes)  examined on two Cirrus HD-OCTs (Carl Zeiss Meditec) sequentially for three days (macular area examinations, 67 patients) and five days (examination of the optic disc region, 62 people), including 17 people who underwent both types of examination. Both the original scanning data (B-scans) and the results of their subsequent analysis were evaluated for the presence of artifacts. Results. The criteria of OCT artifacts were suggested and their practical classification was proposed, which distinguishes three types of artifacts: segmentation errors/errors in delineation of the optic disc borders, "out-of-register" artifacts and displacement/fallout of B-scans, and eight main causes of artifacts. The frequency of artifacts ranged from 19 % (analysis of the optic disc area) to 37 % (analysis of the macular area) and 65 % (evaluation of the ganglion cell-inner plexiform layer). The most common were segmentation errors in patients with pronounced pathology or epiretinal membranes (fibrosis). Conclusion. Clinically significant OCT artifacts occur in 19–65 % of cases, depending on the analyzed eye fundus structures. The most common artifacts are segmentation errors in patients with pronounced pathology and epiretinal membranes (fibrosis). A practical classification of OCT artifacts is proposed, which distinguishes three main types and the most important causes of their presence.